System analysis of fatigue in pilots and co-pilots executing short-hall flight operations - Bennett, Cleo Taylor (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2020)
Background: This study was conducted as part of Denel's South African Regional Aircraft (SARA) development project. Regional aircraft have a maximum flight time of 60 minutes. Hence, the study focuses on matters pertaining to the short-haul flight context. Pilot fatigue has been recognised as a safety concern in the aviation industry. It impacts on pilot performance across the board, not least in the short-haul context. However, the specific factors that lead to pilot fatigue in short-haul operations have not been well researched. Research Aim: To identify and examine the factors which influence pilot/co-pilot fatigue in short-haul aviation contexts. Method: Fatigue is multifaceted, and has multiple definitions and descriptions. It is acknowledged as a complex phenomenon, the development of which is dynamically influenced by various factors. Thus, a systems approach based on the work system model by Smith and Carayon-Sainfort (1989) was adopted for this study. A systems analysis was conducted in two parts: 1) a literature analysis, and 2) expert interviews. Results: Both the literature analysis and the interviews indicated that pilot fatigue in short-haul flight operations represent composite system outcomes influenced by various factors. The factors identified were structured (systematised) into categories, namely organizational factors, task-related factors, environmental factors, factors linked to technology and tools, and non-work-related factors specific to the individual pilot. An example of a task-related factor would be the performance by pilots of multiple take-offs and landings; organizational factors include work time arrangements and duty scheduling (e.g. unpredictable schedule, early starts/late finishes, number of flight sectors in a shift, extended working hours, numerous consecutive work days, standby duties, flight, duty and rest limitations (regulations and guidelines); and short turnaround periods); environmental factors might include the small pressurised cockpit environment, movement restriction, very low humidity, low air pressure, vibrations, high noise levels, low light intensity light, and inclement weather); there are many examples of how tools and technology utilized by pilots might affect their fatigue levels; and finally, pilot-specific non-work-related factors would include things like the pilot's age, health (lifestyle), family stress, work experience and sleep environment. All of these factors were identified during the literature analysis and have a significant bearing on how fatigue could present in short-haul pilots/co-pilots. Other important fatigue-related factors revealed during the expert interviews included, organizational culture, time management, health implications of fatigue, and management of fatigue. Conclusions: Pilot fatigue is a complex and multi-factorial physiological condition. There are many interacting components which contribute to pilot fatigue in short-haul operations. These should be viewed from an integrated perspective and holistic, systems-based approaches should be taken to manage these issues, particularly in the context of short-haul operations. This would optimize pilot performance and well-being and, most importantly, improve the safety of the work environment to enhance overall operation safety. Limitations: The study does not quantify the contributions made to pilot fatigue by the various factors explored. Therefore, care needs to be taken when designing and implementing interventions based on this research.
Keywords: Air pilots -- Health and hygiene; Fatigue; Work environment -- Psychological aspects; Work environment -- Physiological aspects